1977
DOI: 10.1080/00380768.1977.10433040
|View full text |Cite
|
Sign up to set email alerts
|

Allantoin production and its utilization in relation to nodule formation in soybeans

Abstract: A remarkable accumulation and utilization of aUantoin are observed in soybean plant bearing ll~dules (G{ycin, max variety A62-1). To study ita physiological role, changes in activities and distrl.bution of the enzymes concerning the purine catabolism (i.,., xanthine oxidase, uricase, allan-tOinase and allantoicase) were measured during development. d' Uricase activity was found in the radicles in the early stage of seedling development, and no llfi'erence of the enzyme activity was detected between the radicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
1

Year Published

1980
1980
1987
1987

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 13 publications
0
21
1
Order By: Relevance
“…Previous work (18,19) has shown that allantoinase is present in stem and leaf tissue, but prior to this report there has been no information on the presence of ureide-assimilating enzymes in soybean fruits. During leaf Plant Physiol.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Previous work (18,19) has shown that allantoinase is present in stem and leaf tissue, but prior to this report there has been no information on the presence of ureide-assimilating enzymes in soybean fruits. During leaf Plant Physiol.…”
Section: Discussionmentioning
confidence: 57%
“…In plants depending solely on N2 fixation for their N requirements, ureides comprise up to 86% of the xylem sap N (9). Based on enzymic studies, ureides were suggested to be synthesized in nodules and transported to the shoot where they are assimilated (18,19). Ishizuka (7) has suggested that ureide-N, arising predominantly from N2 fixation, is used more efficiently in seed protein production than N in the form of amino acids, amides and nitrate.…”
mentioning
confidence: 99%
“…Work on the enzymes involved in purine degradation has been mainly studied in animals and micro-organisms with little emphasis on the occurrence, properties, and location of these enzymes in plants (Vogels and van der Drift, 1976). In particular there have been only a few reports of allantoic acid-degrading activity in plants (Echevin and Brunei, 1937;van der Drift and Vogels, 1966;Singh, 1968;Hartmann and Arnold, 1974;Tajima, Yatazawa, and Yamamoto, 1977). Following the work of Kushizaki, Ishizuka, and Akamatsu (1964) and Ishizuka, Okino, and Hoshi (1970) who showed that nodulated soyabean plants (Glycine max L.) contain large amounts of ureides, two Japanese groups have published evidence that nodules produce allantoin (Matsumoto, Yatazawa, and Yamamoto, 1977a;Fujihara and Yamaguchi, 1978a).…”
Section: Introductionmentioning
confidence: 99%
“…Following the work of Kushizaki, Ishizuka, and Akamatsu (1964) and Ishizuka, Okino, and Hoshi (1970) who showed that nodulated soyabean plants (Glycine max L.) contain large amounts of ureides, two Japanese groups have published evidence that nodules produce allantoin (Matsumoto, Yatazawa, and Yamamoto, 1977a;Fujihara and Yamaguchi, 1978a). From measurements of the enzymes involved in purine catabolism it was suggested that the allantoin is utilized mainly in the leaves after translocation (Tajima et al, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…In soybean nodules, uricase was reported to be located in the bacteroid away from the other purine oxidation enzymes (27) although the situation apparently was different in cowpea nodules (2). The location of uricase within the nodule tissue would undoubtedly prove to be important, since the pH and 02 requirements for optimum activity of this enzyme seem so different from the conditions which prevail generally in nodules (1,5).…”
Section: Discussionmentioning
confidence: 98%